SINKRONISASI DAN DIFERENSIASI PUTUSAN HAKIM DALAM PENYELESAIAN KASUS-KASUS KEKERASAN DALAM RUMAH TANGGA - Putra Astiti, Tjokorda Istri (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
This study specifically aims to assess synchronization and differentiation between the judge's decision, both horizontally and vertically, especially with regard to domestic violence cases. In addition, this study also intends to study about rule  which are  applied by the Judges on the cases, and  reveal whether the  decision  under review reflects the gender justice This research is a legal normative research using case approach which was examined by studying the Judge’s decision in concrete cases, especially with regard to domestic violence. The number of decisions that were examined are six decisions which consists of three decisions of the District Court (Pengadilan Negeri) and  three decisions  of the High Court (Pengadilan Tinggi). The decisions are determined by purposive sampling.  Based on the analysis of the six decisions mentioned above ,  can be concluded as following: 1)  The rule applied by the judge in hanling the concrete cases  regarding domestic violence particularly violence against women is on the Domestic Violence Act ( Act No. 23/2004 ) with the application of a kind of sanction of imprisonment ranging from 1-3 months, that varied there the defendant was arrested some are dropped with conditional (pidana bersyarat) (not being held prisoner) 2)  Among the three decisions of the District Court and the three decitions of the High Court which have analysed,  in one hand show synchronization and the other hand show differentiation.  In this case, synchronization and differentiation  can be seen vertically (between the District Court and the High Court decision), and horizontally (between the District Court to each other) or between the decision of the High Court to each other).  3)  That the decision of the District and the High Court,  either have reflected gender sensitively and gender equity.
Keywords: Court Decision; Differentiation; Domestic Violence Case; Synchronization